Empirical Evidence of the Relationship Between Regulatory Efficiency, Market Openness, and Bank Productivity in Economies at Different Income Levels: Evidence from Selected Asian and Mena Countries - Fakarudin Kamarudin; Hafezali Iqbal Hussain; Nazratul Aina Mohamad Anwar; Janusz Michałek; Mohd Shahril Ahmad Razimi (Institute of Economic Research (Poland), 2025)
Indexed by Scopus